Evaluating the potential of green roofs incorporating coconut waste for climate change adaptation - Noor Suraya, Romali; Sawant, Vishwas A. (Penerbit UTHM, 2025)
Climate change is a pressing global issue demanding urgent attention due to its widespread impacts. Green roofs present a promising solution by improving stormwater management, enhancing thermal regulation, and promoting sustainability. Yet, their adoption in Malaysian buildings remains limited. The lack of recycled waste utilization also reflects a missed opportunity for sustainable innovation. Coconut waste, abundantly available in Malaysia, remains unexploited despite its potential as a green infrastructure component. Hence, experimental investigations were conducted using three roof models: a conventional roof, a green roof constructed with commercial materials, and a green roof incorporating recycled waste. In the recycled waste-based green roof, coconut shells were used as the drainage layer, while coconut fibers served as the filter layer. Results showed that the recycled waste green roof outperformed the commercial green roof, reducing peak flow by up to 46%, compared to 19–31% for the commercial green roof. It also enhanced stormwater quality, achieving a 45% reduction in biochemical oxygen demand (BOD), while the commercial green roof achieved only 5%. Additionally, vegetated roofs helped lower temperatures, with reductions ranging from 6.45% to 11.48% for the commercial green roof and from 14.75% to 16.13% for the recycled waste green roof, compared to the conventional roof. These findings highlight the potential of green roofs, particularly those utilizing recycled waste materials, as a sustainable solution for urban climate adaptation. Increased adoption of such systems can help to address environmental challenges while promoting the circular use of waste materials.